THE INFLUENCE OF LIQUIDITY AND COMPANY SIZE ON THE VALUE OF AUTOMOTIVE SUBSECTOR COMPANIES IN THE INDONESIAN STOCK EXCHANGE - Maradu Ariguna Hutajulu; Dian A. S. Prawansa; Andi Reni (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
The valuation of companies holds a pivotal role in determining the wealth of shareholders. In the context of the automotive subsector within the Indonesian capital market, understanding the factors that influence company value is of significant interest for investors and stakeholders alike. Two key variables under scrutiny in this research are liquidity and firm size. Liquidity denotes the ability of assets to be readily converted into cash without causing substantial price disruptions, while firm size relates to the scale and scope of a company's operations. This study seeks to investigate the impact of liquidity and firm size on the company value of firms listed on the Indonesia Stock Exchange, specifically within the automotive subsector. The data utilized in this research is quantitative, and the literature review technique is employed to gather data and document research outcomes. The research findings indicate that liquidity has a positive and significant impact on the company value of firms listed on the Indonesia Stock Exchange, particularly in the automotive subsector. On the other hand, firm size also has a positive effect on the company value in the automotive subsector in the Indonesian stock market, but it is not statistically significant.